RESPIRACIÓN ARTIFICIAL DE RICARDO PIGLIA: UNA REFORMULACIÓN DE LA NOVELA DE ARTISTA TRAS EL FIN DE LAS UTOPÍAS. - del Yerro, Inmaculada Donaire (Revista Chilena de Literatura)
This paper proposes a reading of Artificial respiration (1980) by Ricardo Piglia as an artist novel, according to Herbert Marcuse's definition, validated for Latin American artist novels written at the end of the nineteenth century. The most influential critical studies have focused on that period. In this paper, the representation of the writer in Artificial respiration is compared with its corresponding representation at the end of the nineteenth century. This comparison allows us to highlight, on the one hand, the survival of the artist's novel as an answer to the purpose of the literature after the end of the utopias. And on the other hand, the literary change carried out by Piglia: his reformulation of the character of the writer and also of the artist novel by employing narrative methods coming from the detective subgenre.